## Simplifying the Equation: (x)+(x+3)+(x-2)+3(x+3)-1=87

This equation can be simplified to have fewer terms and make solving for *x* easier.

Here's how we can do it:

**Distribute:**- Start by distributing the 3 in the term 3(x+3): 3(x+3) = 3x + 9

**Combine Like Terms:**- Identify the terms with
*x*and the constant terms: (x) + (x+3) + (x-2) + 3x + 9 - 1 = 87 - Combine the
*x*terms: x + x + x + 3x = 6x - Combine the constant terms: 3 - 2 + 9 - 1 = 9

- Identify the terms with
**Rewrite the Equation:**- The simplified equation becomes:
**6x + 9 = 87**

- The simplified equation becomes:

Now, the equation has fewer terms and is easier to solve for *x*.